Bacterial Profile and Antibiotic Use in Catheter-Associated Urinary Tract Infection Patients at a Tertiary Referral Hospital in Surabaya, Indonesia - Erianto, Ahmad Veri; Asmarawati, Tri Pudy; Widodo, Agung Dwi Wahyu; Rachman, Brian Eka (Folia Medica Indonesiana, 2023)
Highlights: • This study examined patients with catheter-associated urinary tract infections (CAUTI) to find the prevalent bacteria and the frequency of antibiotic use. • Extended-spectrum beta-lactamase (ESBL)-producing Escherichia coli sensitive to amikacin was found to be the most common pathogen in CAUTI, while ceftriaxone was the most commonly used antibiotic. Abstract Catheter-associated urinary tract infection (CAUTI) is the most typical type of infection associated with healthcare. This infection constitutes a significant health problem due to its complications and frequent recurrence. The high annual incidence of CAUTI leads to infectious complications and a high cost of treatment. Antibiotic-resistant bacteria further complicate the problem because multiresistant pathogenic bacteria are often responsible for these infections. Moreover, the lack of a comprehensive case reporting system in Indonesia hinders the determination of CAUTI incidence. This study aimed to determine the bacterial profile and antibiotic use in CAUTI patients (n=22) at the Internal Medicine Inpatient Unit of Dr. Soetomo General Academic Hospital, Surabaya, Indonesia. This retrospective descriptive study collected data from patient medical records to describe the incidence, type of bacteria, sensitivity patterns, and antibiotic use in CAUTI patients. The data collection process included collecting medical records, recording information on data collection sheets, and recapitulating and analyzing the data. The criteria for CAUTI diagnosis were a bacterial count of â‰¥105 CFU/mL and a catheterization that lasted more than 48 hours. Samples were selected using non-probability sampling, also known as saturation sampling. Meanwhile, variables analyzed in this study were the type of pathogenic bacteria, antibiotics used, age, and sex. Descriptive analysis was employed to analyze the data. The findings suggested that the most common bacteria were Escherichia coli, with eight of nine bacteria showing extended-spectrum beta-lactamase (ESBL) production. Female patients aged 35–65 years were the majority of the CAUTI patients. Amikacin was the antibiotic with the highest sensitivity (90.9%), while ceftriaxone was the most common type of antibiotic administered to the patients. In addition, intravenous (IV) administration was the most common route of antibiotic administration, with an average therapy duration of seven days. In conclusion, identifying the type of pathogenic bacteria and performing antibiotic susceptibility testing can help minimize antibiotic resistance and prevent more severe complications in CAUTI patients.